2021
DOI: 10.3389/fmicb.2021.752537
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Profiling in Mycobacterium Provides Insights Into Stress Adaptability

Abstract: Mycobacteria encounter a number of environmental changes during infection and respond using different mechanisms. Small RNA (sRNA) is a post-transcriptionally regulatory system for gene functions and has been investigated in many other bacteria. This study used Mycobacterium tuberculosis and Mycobacterium bovis Bacillus Calmette-Guérin (BCG) infection models and sequenced whole bacterial RNAs before and after host cell infection. A comparison of differentially expressed sRNAs using Gene Ontology (GO) and Kyoto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In Mycobacterium, numerous sRNAs differentially affect bacterial viability in hostlike conditions. [25][26][27] In the present study, we discovered that overexpression of sRNA21 in M. abscessus ATCC_19977 resulted in an increased ability to infect macrophages and significantly induced resistance to oxidative stress in vitro. Biofilm plays an important role in M. abscessus pathogenicity and also drug resistance, and the biofilmforming ability influences bacterial existence in adverse environments.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In Mycobacterium, numerous sRNAs differentially affect bacterial viability in hostlike conditions. [25][26][27] In the present study, we discovered that overexpression of sRNA21 in M. abscessus ATCC_19977 resulted in an increased ability to infect macrophages and significantly induced resistance to oxidative stress in vitro. Biofilm plays an important role in M. abscessus pathogenicity and also drug resistance, and the biofilmforming ability influences bacterial existence in adverse environments.…”
Section: Discussionmentioning
confidence: 57%
“…Because overexpression of sRNA21 improved bacterial growth viability the most among all recombinant strains, we chose to investigate the role of sRNA21 in M. abscessus further. In Mycobacterium , numerous sRNAs differentially affect bacterial viability in host‐like conditions 25–27 . In the present study, we discovered that overexpression of sRNA21 in M. abscessus ATCC_19977 resulted in an increased ability to infect macrophages and significantly induced resistance to oxidative stress in vitro.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Early pathogen-specific M. tuberculosis transcriptome studies [ [26] , [27] , [28] ] further indicated regulation of stress-response pathways and unique gene regulation profiles associated with clinical isolates of MTBC, implying strain-specific transcriptional regulatory mechanisms. Furthermore, NGS technologies have recently identified many other regulatory non-coding sRNAs [ [29] , [30] , [31] , [32] , [33] , [34] ], and MTBC-specific methylation patterns [ [35] , [36] , [37] , [38] , [39] , [40] , [41] ] that govern the molecular networks of these notorious pathogens. Therefore, the current review provides an update on all the known non-coding regulatory RNAs and their associated transcripts, together with the methylome data of M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%